Transformation of Upgrading MSMEs to Implementation Studies - Himlina, Himlina; Asmorowati, Sulikah; Setijaningrum, Erna (Universitas Muhammadiyah Gorontalo, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in economic growth, job creation, and innovation, both in Indonesia and in other countries such as India. Although MSMEs make a significant contribution to industrial output and employment, this sector still faces challenges such as limited financing, technology adoption, and market access. The government is trying to overcome these obstacles through funding, incentives, and regulatory simplification. Indonesia is recorded as the country with the largest number of MSMEs in ASEAN, with significant contributions to GDP and national workforce absorption. This study highlights efforts to strengthen MSMEs in Banyuwangi Regency through the